2013
DOI: 10.3904/kjim.2013.28.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Insulin secretion and insulin resistance in Korean women with gestational diabetes mellitus and impaired glucose tolerance

Abstract: Background/AimsThe aim was to compare the insulin sensitivity and secretion index of pregnant Korean women with normal glucose tolerance (NGT), gestational impaired glucose tolerance (GIGT; only one abnormal value according to the Carpenter and Coustan criteria), and gestational diabetes mellitus (GDM).MethodsA cross-sectional study was performed with 1,163 pregnant women with positive (1-hour plasma glucose ≥ 7.2 mmol/L) in a 50-g oral glucose challenge test (OGCT). The 100-g oral glucose tolerance test (OGTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 22 publications
3
19
0
1
Order By: Relevance
“…Yang et al [5] found that the insulin resistance indices were significantly worse in the GDM group than in the GIGT group, as expected. However, the insulin levels at each time point in the 100-g OGTT and the area under the curve for insulin were significantly higher in the GIGT group than in the GDM group.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Yang et al [5] found that the insulin resistance indices were significantly worse in the GDM group than in the GIGT group, as expected. However, the insulin levels at each time point in the 100-g OGTT and the area under the curve for insulin were significantly higher in the GIGT group than in the GDM group.…”
supporting
confidence: 58%
“…However, recent studies showed that the maternal and fetal outcomes are poorer if GIGT is not treated [3,4]. In this issue of The Korean Journal of Internal Medicine , Yang et al [5] analyzed various indices of insulin resistance and insulin secretion in 1,163 pregnant Korean women undergoing 100-g OGTT. Based on the OGTT results, the study subjects were subdivided into three groups: NGT, GIGT (only one abnormal value based on the criteria of Carpenter and Coustan), and GDM.…”
mentioning
confidence: 99%
“…East Asians have a relatively low body mass index (BMI), and the underlying pathophysiology of diabetes in this population is thought to differ from that in other ethnicities [39]. In previous studies, the development of diabetes in Korean individuals was attributed to a genetic predisposition to β-cell dysfunction and/or impaired β-cell compensation to insulin resistance [40,41].…”
Section: Postpartum Diabetes In Women With Previous Gdmmentioning
confidence: 99%
“…while BMI and UCPS120 are noninvasive ones. HOMA-IR and Matsuda index had better predictions for GDM in previous studies [11,12].…”
Section: Discussionmentioning
confidence: 58%